Diversity of ndo Genes in Mangrove Sediments Exposed to Different Sources of Polycyclic Aromatic Hydrocarbon Pollution - Gomes, Newton C. Marcial (American Society for Microbiology (ASM), 2007)
Polycyclic aromatic hydrocarbon (PAH) pollutants originating from oil spills and wood and fuel combustion are pollutants which are among the major threats to mangrove ecosystems. In this study, the composition and relative abundance in the sediment bacterial communities of naphthalene dioxygenase (ndo) genes which are important for bacterial adaptation to environmental PAH contamination were investigated. Three urban mangrove sites which had characteristic compositions and levels of PAH compounds in the sediments were selected. The diversity and relative abundance of ndo genes in total community DNA were assessed by a newly developed ndo denaturing gradient gel electrophoresis (DGGE) approach and by PCR amplification with primers targeting ndo genes with subsequent Southern blot hybridization analyses. Bacterial populations inhabiting sediments of urban mangroves under the impact of different sources of PAH contamination harbor distinct ndo genotypes. Sequencing of cloned ndo amplicons comigrating with dominant DGGE bands revealed new ndo genotypes. PCR-Southern blot analysis and ndo DGGE showed that the frequently studied nah and phn genotypes were not detected as dominant ndo types in the mangrove sediments. However, ndo genotypes related to nagAc-like genes were detected, but only in oil-contaminated mangrove sediments. The long-term impact of PAH contamination, together with the specific environmental conditions at each site, may have affected the abundance and diversity of ndo genes in sediments of urban mangroves.